Developed method for producing fish protein concentrate from marine fish tongue sole Cynoglossus bilineatus - Al-Hassoon, Ahmed Shihab; Al-Faiez, Nawres AbdulGhany; Al-Hamdany, Qusay Hamid (Iraqi Journal of Aquaculture, 2022)
The aim of this study was to produce fish protein concentrate from marine fish Cynoglossus bilineatus, the fish brought from local Basrah market and dried in the oven at 025 °C for 06 h. The chemical composition of the dried fish were 48.62 % protein (N×6.25), 19.49 % fat and 19.95 % ash, while for the processed protein concentrate were 79.56 % protein (N×6.25), 6.38 % fat and 9.51 % ash. The obtain yield was 67.58 % of dried fish. The processed product characterized with light brown and acceptable fishy smell, and also showed good strong stability after 90 days of storage regarding to TVNB, TBA and total bacterial count at 28 °C, 10 °C and -4 °C without objectionable changes in color and smell. The processed product also had low total bacterial count which was 487, 481 and 462 CFU/gm for the temperatures and storage time above respectively, as well as, coliform bacteria was not detected. The total volatile nitrogen bases were 8.4, 8.2 and 8.0 mg N/ 100 gm, while the TBA were 0.628, 0.266 and 0.263 mg malon aldehyd / kg for the same temperatures and storage time respectively.